WYBRANE MODELE NADZORU BANKOWEGO FUNKCJONUJĄCE W EUROPIE - Frysztak, Małgorzata (Wydział Prawa i Administracji UAM, 1998)
Banking activity is a kind of economic activity which is submitted to strict reglamentation and control. This supervision is exercised by subjects o f very different status and equally different possibilities of reacting in the role of a surveyor. The Author discusses types and conditions of functioning o f control organs in chosen countries: France, Germany, Italy, Switzerland and Great Britain. Following types of supervision are treated in the article: supervision by internal organs of a bank, owner’s supervision, supervision by boards of auditors as well as supervision made by subjects independent on banks structures - including State control institutions.
CHOSEN EUROPEAN MODELS OF BANKS SUPERVISION